Overreaction through Anchoring - Constantin Bürgi; Julio L. Ortiz (Center for Economic Studies and ifo Institute (CESifo), 2022)
We show that updates to macroeconomic expectations among professional forecasters exhibit an offsetting pattern where increases in current-quarter predictions lead to decreases in three quarter ahead predictions. We further document evidence of individual overreaction at the quarterly frequency and a lack of overreaction at the annual frequency. We explain these facts with a model of annual anchoring in which quarterly predictions must be consistent with annual predictions. We estimate our model to fit survey expectations and show that it provides a unified explanation for our empirical facts. Furthermore, our model yields frequency-specific estimates of information frictions which imply a larger role for inattention at the annual frequency.
Keywords: C53; D83; D84; E17; E27; E37; E47; 330; information friction; consistency; SPF; inattention; overreaction